ENGELOLAAN PUPUK ORGANIK DAN PUPUK ANORGANIK TERHADAP PRODUKSI TANAMAN JAGUNG MANADO KUNING ( Zea mays L) - Harinda Yonathan Efraim; Mamarimbing Rinny; Porong Jelie V. (Universitas Sam Ratulangi, 2017)
ABSTRACT The aim of this research was to study the production of Manado Kuning corn. With aplication of organic and inorganic fertilizers and also to know the good fertilizers dosage the good production. The research was undertaken in Kalasey village, Minahasa regency from april to agust 2016. Research is organised use design random group. With five levels of fertilizers dosage. ( P1 = inorganic fertilizers 300 Kg / Ha NPK and 300 Kg / Ha Urea, P2 = inorganic fertilizers 225 kg / Ha NPK and 225 Kg / Ha Urea + 7,5 ton / Ha Compost, P3= inorganic fertilizers 150 kg / Ha NPK and 150 kg/ Ha Urea + 10 Ton / Ha Compost, P4 = Inorganic fertilizers 75 Kg / Ha NPK and 75 Kg / Ha Urea + 12,5 Ton / Ha Compost, P5= Organic fertilizers 15 Ton / Ha Compost ) The result showed that P4 treatment ( 25 % Inorganic fertilizers + 75 % organic fertilizers ) has the highest production compared with other treatment. The high production Manado Kuning corn obtained from treatment P4 (Inorganic fertilizers 75 Kg / Ha NPK and 75 Kg / Ha Urea + 12,5 Ton / Ha Compost) caused by availability adequate nutrient to support production. Deficient inorganic fertilizers can overcome by organic fertilizers, so organic fertilizers and inorganic fertlizers very good for in aply simultaneously. For increasing production Manado Kuning corn suggested to use fertilizing dosage 75 Kg / Ha NPK and 75 Kg / Ha Urea + 12,5 Ton / Ha Compost Keywords : Fertilizers organic and inorganic, Manado Kuning corn